Effect of reactor height/diameter ratio and organic loading rate on formation of aerobic granular sludge in sewage treatment - Awang, N.A.; Shaaban, M.G. (Elsevier, 2016)
Although a high volume of research on aerobic granular sludge exists in the body of related literature, the determination of biokinetic parameters of aerobic granules using a linear plot for biodegradation of real wastewater has rarely been discussed. Therefore, this study aims to determine the biokinetic parameters of aerobic granules that develop in a sequencing batch reactor (SBR) with sewage as a substrate, using a linear plot. The difference in biokinetic parameter (k, Ks, Y, Kd and μmax) values gathered from five aerobic granules batches were tested as whether it is linearly correlated with the variable organic loading rate (OLR) and reactor height/diameter (H/D) ratio. The R2 value of 0.97 and 0.82 was obtained from the linear correlation between μmax and reactor H/D ratio, and Y and OLR, respectively. This demonstrates that biomass production (Y and μmax) proportionally depends on the increase in OLR and reactor H/D ratio. This might be because the effectiveness of the aerobic granules measured by Ks are greater in high H/D ratio reactors with values over 315 mg/L as compared to less than 276 mg/L in low H/D ratio reactors.